PENGARUH KUALITAS LAYANAN KARYAWAN, PERSEPSI HARGA, DAN LOKASI TERHADAP KEPUASAN PELANGGAN JNE (Studi Pada Mahasiswa UNISBANK Semarang) - Sony Sukmala, 12.05.51.0161; Sutejo, Bambang (Students Journal of Economic and Management, 2016)
Companies that want to survive in the competitive market should be able to deliver services in accordance with the wishes of consumers. The companys survival depends on the ability of companies to build long-term relationships with customers in order to create a good view of the quality and brand of the product or service itself. So the quality of service is essential in order to meet customer satisfaction. Quality has a close correlation with the customer satisfaction. Quality provides an impetus to consumers to establish a strong bond with the company. This study focus about is influence of service worker quality, perceived price, and location of customer satisfaction (Study on UNISBANK Semarang Student as JNE Customers). This research is a explanative research. The samples are Economics and Business Faculty students are 96 respondents. The research instrument used questionnaire. Analysis of data using multiple linear regression. The results showed that the quality of service, perception of price, location and positive effect on customer satisfaction. Keywords: service quality workers, perceived price, location, customer satisfaction